고환고정술을 받는 소아 환자에서 미추 차단시 로피바케인과 덱사메타손 병합과 로피바케인 단독 사용의 술 후 진통효과 비교 - 김은미 (The Graduate School, Ajou University, 2015)
Introduction: Epidural administration of dexamethasone might reduce postoperative pain in adults. We evaluated whether a caudal block of 0.1 mg/kg dexamethasone combined with ropivacaine improves analgesic efficacy in children undergoing day-case orchiopexy. Methods: This randomized, double-blind study included 80 children aged 6 months to 5 yr who underwent day-case, unilateral orchiopexy. Patients received either 1.5 ml/kg of 0.15% ropivacaine (Group C) or 1.5 ml/kg of 0.15% ropivacaine in which dexamethasone of 0.1mg/kg was mixed (Group D) for caudal analgesia. Postoperative pain scores, rescue analgesic consumption, and side-effects were evaluated 48 h after operation. Results: Postoperative pain scores at 6 and 24 h post-surgery were significantly lower in Group D than in Group C. Furthermore, the number of subjects who remained pain free up to 48 h after operation was significantly greater in Group D [19 of 38 (50%)] than in Group C [4 of 37 (10.8%); P<0.001]. The number of subjects who received oral analgesic was significantly lower in Group D [11 of 38 (28.9%)] than in Group C [20 of 37 (54.1%); P=0.027]. Time to first oral analgesic administration after surgery was also significantly longer in Group D than in Group C (P=0.014). Adverse events after surgery including vomiting, fever, wound infection, and wound dehiscence were comparable between the two groups. Conclusion: The addition of dexamethasone 0.1 mg/kg to ropivacaine for caudal block can significantly improve analgesic efficacy in children undergoing orchiopexy. Keyword: Caudal anaesthesia, Children, Dexamethasone, Orchiopexy, Postoperative analgesia
학위논문(박사)--아주대학교 일반대학원 :의학과,2015. 2
Keywords: Caudal anaesthesia; Cildren; Dexamethasone; Orchiopexy; Postoperative analgesia